PROFILE OF PUBLICATIONS ON THE WORK IN URBAN CLEANING (Fiep Bulletin - online, 2016)
Objective: To analyze the profile of publications on the work on urban sanitation. Method: This is an integrative review, carried out in the periods from September to October 2015, starting from the choice of subject, the definition of the research question and keyword selection based on Medical Subject Headings - Urban Cleansing. From this and the inclusion and exclusion criteria, eight publications constituted the sample. Results: There are few publications that portray approaches relating to urban cleaning, likewise, most were found in the Latin American and Caribbean database (62.5%; n = 5), Portuguese (87.5%; n = 7) and published before 2011 (75.0%; n = 6), showing the downgrade of publications. In contrast, as contemplated core theme was impact of the work process on health / worker disease (50.0%; n = 4). Conclusion: From the evidence, it expected that this work could serve as a source of knowledge and information about the subject matter and awaken the interest of researchers in effect research in the area covering essentially the dichotomy public cleaning versus worker's health, in favor promoting the health of workers of the area.
Keywords: Work. Urban Cleaning. Profile.